PENGARUH METODE PEMBELAJARAN HOME VISIT DAN PEMBERIAN TUGAS TERHADAP HASIL BELAJAR MATEMATIKA DI KELAS VII SMP PADAMU NEGERI T.A 2020/2021 - Ropinus Sidabutar (JGK (Jurnal Guru Kita), 2022)
Abstract: The Effect of Home Visit Learning Methods and Giving Assignments on Mathematics Learning Outcomes in Class VII SMP Padamu Negeri 2020/2021. The purpose of this study was to determine the effect of student learning outcomes who received learning using the home visit method and learning with the assignment method on the eye. Mathematics lessons in class VII SMP Padamu Negeri in Medan city FY 2020/2021. This type of research is a quantitative descriptive research. The population used in this study were all students of class VII SMP Padamu Negeri totaling 60 students consisting of 2 classes. Sampling in this study was using a sampling technique, where the sample amounted to 60 divided into two groups, the experimental group I with a total of 30 students and the experimental group II with a total of 30 students. The tool used in data collection is a multiple choice test consisting of 20 questions to measure student learning outcomes. The data analysis technique in this study used normality, homogeneity, and hypothesis testing using the t-test formula. Based on data analysis, the average value of learning outcomes for the Home Visit learning method is 80.93 and the value of learning outcomes for the assignment-giving learning method is 74.68. From the results of the data analysis requirements test, the population is normally distributed and has a uniform variance (homogeneous) and the results of hypothesis testing show Ho is rejected and Ha is accepted with the results of tcount > ttable, namely 2.46 > 1.87. The researcher concluded that there was an effect using the Home Visit and Assignment learning methods on mathematics learning outcomes in Class VII SMP Padamu Negeri T.A 2020/2021. Keywords: Learning Outcomes, Home Visit Method, Assignment Method